(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2021)
This work presents the design and finite element analysis of a surface acoustic wave (SAW)-based sensor for the detection of volatile organic compound (VOC) gases. The effect of silicon nanowire array (SiNWA) on a 128º YX-lithium niobate (LiNbO3) substrate for sensing the VOC gases was simulated using COMSOL Multiphysics. The frequency response was investigated in relation to changes in the SiNWA sensitive layer and VOC gas concentration. The resonant frequency of the SAW device was also evaluated, and simulation results were obtained after being exposed to 100ppm concentration of VOC gas. It was determined that the frequency increased, after the sensor was exposed to VOC gases. In general, extending the length of the SiNWA enhances the sensor’s sensitivity.